2022
DOI: 10.3390/vaccines10010115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dental Anxiety While Visiting Dental Clinics before and after Getting Vaccinated in Midst of COVID-19 Pandemic

Abstract: Vaccination is critical to control the rate of coronavirus transmission and infectivity. Dental practices are a high-risk area for contracting coronavirus; this fact generates psychological disturbances amongst patients. In this study, we aimed to assess the levels of anxiety of patients while visiting dental practices before and after getting vaccinated. This cross-sectional study was carried out between March and December 2021. An electronic survey was distributed among the vaccinated individuals who visited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…Studi yang dilakukan Lal et al, menyatakan vaksinasi dapat menurunkan tingkat kecemasan dan ketakukan masyarakat untuk berobat ke dokter gigi. Namun, tindakan pencegahan lain tetap harus dilaksanakan meskipun dokter gigi ataupun pasien telah menerima vaksinasi (Lal et al, 2022).…”
Section: Kajian Pustakaunclassified
“…Studi yang dilakukan Lal et al, menyatakan vaksinasi dapat menurunkan tingkat kecemasan dan ketakukan masyarakat untuk berobat ke dokter gigi. Namun, tindakan pencegahan lain tetap harus dilaksanakan meskipun dokter gigi ataupun pasien telah menerima vaksinasi (Lal et al, 2022).…”
Section: Kajian Pustakaunclassified
“…In a study conducted in Pakistan with a sample of dental patients, 54.0% reported not suffering from COVID‐19‐like symptoms, and 25.0% thought that the environment of a dental clinic was the source of a high risk of infection of the virus. However, after the vaccination of the patients, a decrease in dental anxiety scores was found 13 . In another study conducted in Hong Kong, adult residents reported low levels of mental health problems after the COVID‐19 vaccination 14 .…”
Section: Introductionmentioning
confidence: 96%
“…However, after the vaccination of the patients, a decrease in dental anxiety scores was found. 13 In another study conducted in Hong Kong, adult residents reported low levels of mental health problems after the COVID‐19 vaccination. 14 About 13% and 17% lower odds of anxiety and depression, respectively, were found in those participants who received the COVID‐19 vaccine than those who did not, as per a study conducted in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, so as to manage the anxieties related with contracting COVID-19, vaccinations have been advised by several organizations to battle mortalities and morbidities related to SARS-CoV-2 infection. In this editorial, we focused on the study by Lal et al, titled "Comparison of dental anxiety while visiting dental clinics before and after getting vaccinated in midst of COVID-19 pandemic" [12]. In this study by Lal et al, the authors intended to evaluate the anxiety levels of patients before and after getting vaccinated while visiting dental clinics amidst the COVID-19 pandemic [12].…”
mentioning
confidence: 99%
“…In this editorial, we focused on the study by Lal et al, titled "Comparison of dental anxiety while visiting dental clinics before and after getting vaccinated in midst of COVID-19 pandemic" [12]. In this study by Lal et al, the authors intended to evaluate the anxiety levels of patients before and after getting vaccinated while visiting dental clinics amidst the COVID-19 pandemic [12]. We commend the authors for a well-written, clear and concise manuscript that has an excellent study design with good confidence of interval and sample size.…”
mentioning
confidence: 99%